THE USE OF PUNCTUATION MARKS IN THE ORIGINAL UZBEK TRANSLATION OF ANTOINE SAINT-EXUPERY’S FAIRY TALE "THE LITTLE PRINCE". - M.M.Jurayeva; Daniyorova Barchinoy Absattarovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
This article highlights the use of punctuation when we translate works of art. In this article, we are looking for an answer to the question of whether punctuation marks are correct in translation, that is, when the translator is translating. The article explains the meaning of comma and period.